The impact of innovation, corporate social responsibility, environmental practices, and organizational culture on organizational sustainability - Ichdan, Dany Amrul; Maryani, Maryani (goodwood publishing, 2024)
Purpose: This study analyzes how corporate social responsibility (CSR), innovation, and environmental policies influence organizational sustainability. It also examines how organizational culture mediates these factors to enhance overall performance. Research Methodology: This study employed a quantitative research design and distributed structured questionnaires to employees and managers in various industries. The data were analyzed using Structural Equation Modeling (SEM) to assess the relationships between the independent variables (innovation, CSR, and environmental practices), mediating variable (organizational culture), and dependent variable (organizational sustainability). Results: The findings show that Environmental practices, CSR, and innovation significantly improve organizational sustainability. The relationship between these independent variables and organizational performance was found to be mediated by organizational culture. In particular, a strong organizational culture amplifies the benefits of these factors on performance, indicating that cultivating a strong culture is essential for attaining sustainability. Contribution: This study advances our understanding of organizational sustainability by presenting data on important factors and the mediating function of organizational culture. This provides practitioners and policymakers with helpful ideas on how to use these characteristics to enhance performance. Originality: A comprehensive model of organizational sustainability was created by combining five independent, mediating, and dependent variables. It presents a fresh viewpoint on how internal variables amplify the influence of sustainability drivers by highlighting the function of organizational culture and offering a comprehensive strategy for enhancing sustainability.